Penyimpangan Budaya Dan Kriminalitas: Studi Teoretis Terhadap Teori Subkultural Dalam Kriminologi - Satria, Gagah; Yusuf, Hudi (Veteran Law Review, 2025)
The klithih phenomenon in Yogyakarta represents a form of street violence perpetrated by adolescents, particularly students, through random acts against the public. This phenomenon should not be viewed merely as juvenile delinquency but also as an expression of cultural deviance rooted in social inequality and structural alienation. This study aims to analyze the klithih phenomenon through the lens of subcultural theory in criminology, particularly the perspectives of Albert Cohen, Cloward & Ohlin, and Walter Miller. The research employs a qualitative-descriptive approach based on an in-depth literature review. The findings reveal that klithih perpetrators establish their own group norms that deviate from mainstream societal values as a form of resistance against the education system, family, and broader society, which they perceive as excluding them from social spaces. Thus, klithih behavior can be understood as an attempt to seek identity, solidarity, and recognition within the context of a deviant subculture. This study recommends community-based preventive approaches, educational reform, youth empowerment, and sustained social interventions as more effective solutions than purely repressive measures.